Academic intellectual capital scale: A validity and reliability study - ÇETİN, MÜNEVVER (My University, 2022)
The aim of this study was to develop a scale instrument for measuring academic intellectual capital in the Turkish higher education context depending on student perceptions. The sample consisted of students of higher education institutions in the 2020-2021 academic year. Data were gathered in two stages. Exploratory Factor Analysis (EFA) was conducted in the first stage and Confirmatory Factor Analysis (CFA) was conducted in the second stage. The EFA sample consisted of 538 students studying in 96 higher education institutions while the CFA sample consisted of 492 students studying in 112 higher education institutions. Principal Axis Factoring (PAF) extraction and Promax rotation methods were used in EFA. Results of EFA showed that the scale had a three-factor structure with 20 items. The three-factor structure was confirmed with CFA. Cronbach\"s alpha, stratified alpha, Composite Reliability and McDonald\"s omega were calculated in order to determine the reliability of the scores obtained from the scale. Item discrimination was verified by calculating item-total correlation and item-remainder correlation. Also, t-test was carried out between upper and lower 27% to check item discrimination. Analyses were conducted making use of R (ver. 4.1.2) and RStudio (ver. 2021.09.1 build 372). Overall, results showed that the structure of Academic Intellectual Capital Scale was valid. The measurement tool was concluded to have three factors and 20 items, all in affirmative form.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); General Social Sciences; Social Sciences & Humanities; Academic intellectual capital; Intellectual capital; Higher education; CONFIRMATORY FACTOR-ANALYSIS; EXPLORATORY FACTOR-ANALYSIS; CRITICAL-VALUES; PERFORMANCE; UNIVERSITIES; SATISFACTION; KNOWLEDGE; ALPHA; MODEL; Academic intellectual; capital; Intellectual capital; Higher education